(untitled) (Journal of Fatima Jinnah Medical University, 2023)
Background: Persistent elevation of parathyroid hormone (PPTH) levels following curative parathyroidectomy is a dynamic & multifactorial process. This study was designed to study the frequency of persistent hyperparathyroidism in our patients and to identify the potential causal factors for persistent PTH elevation following parathyroidectomy. Methodology: The study included prospectively collected data on post-operative patients of primary hyperparathyroidism who underwent parathyroidectomy from 2004-2018. Data was analyzed by SPSS version-21. For descriptive statistics, frequency and percentages were calculated, while mean ±standard deviation were calculated for age, duration of disease, pre-operative and post-operative biochemical parameters, like serum PTH, calcium and vitamin D levels. Results: A total of 11 (39.3%) patients, were diagnosed as persistent hyperparathyroidism, out of the 30 patients, who underwent parathyroidectomy. All patients were female with a mean age of 45.27+17.2 years and a mean duration of symptoms of 21.3 months. The mean post-operative PTH level, vitamin D and calcium were 154.04±78.64 pg/ml, 22.28±13.79 ng/ml 9.46±0.79 mg/dl, respectively. Fluctuation of PTH hormone in relation to erratic vitamin D intake was reported in 8 patients, and recurrent parathyroid adenoma was reported in three patients, which was subsequently re-operated. Conclusion: Adequate vitamin D supplementation is essential in the pre and post-operative period to prevent persistent parathyroid stimulation and possible dysregulation. Surveillance for recurrence of hyperparathyroidism should be maintained long term.